Effects of Six Weeks of Medicine Ball Training on Throwing Velocity, Throwing Precision, and Isokinetic Strength of Shoulder Rotators in Female Handball Players. Issue 7 (July 2015) - Raeder, Christian; Fernandez-Fernandez, Jaime; Ferrauti, Alexander
Abstract : Abstract: Raeder, C, Fernandez-Fernandez, J, and Ferrauti, A. Effects of six weeks of medicine ball training on throwing velocity, throwing precision, and isokinetic strength of shoulder rotators in female handball players. J Strength Cond Res 29(7): 1904–1914, 2015—The aim of this study was to investigate the effects of 6 weeks of medicine ball training (MBT) on throwing velocity, throwing precision, and isokinetic strength of shoulder rotators in competitive female handball players. Twenty-eight players (mean ± SD ; age: 20.8 ± 3.3 years, height: 170.5 ± 5.6 cm, body mass: 65.2 ± 8.0 kg) were randomly assigned to an MBT group (TG; n = 15) and a control group (CG; n = 13). TG performed a supervised MBT program, 3 times a week for a total of 6 weeks, focusing on handball-specific movement patterns. Both groups, TG and CG, also conducted a supervised shoulder injury prevention program with elastic tubes, as part of the warm-up, finishing with regular handball throws. Results showed a significant group × time interaction in throwing velocity ( p < 0.001) with the TG posttest results being significantly higher compared with CG ( d = 2.1), and also a significant main time effect ( p < 0.001), with an increase in throwing velocity of 14% ( d = 3.0) and 3.7% ( d = 0.3) for both TG and CG, respectively. Throwing precision did not significantly differ between groups and time points. Isokinetic strength measures revealed a significant group × time interaction ( p ⩽ 0.05) with the TG posttest results being significantly higher compared with CG ( d = 0.9) and also a significant main time effect ( p < 0.01) with an increase of 15% ( d = 0.9) in concentric shoulder internal rotation at 180°·s −1 in the dominant arm in TG, whereas no significant changes occurred in CG. The present results indicate that 6 weeks of MBT elicit significant improvements in functional performance (i.e., throwing velocity) in female handball players, whereas throwing precision remained unaffected. Medicine ball training exercises seem to be a useful and inexpensive strength training strategy in enhancing functional performance by closely mimicking sport-specific movement activities.